Cuicatec ethnozoology: traditional knowledge, use, and management of fauna by people of San Lorenzo Pápalo, Oaxaca, Mexico - Leonor Solís; Alejandro Casas (BMC, 2019)
Abstract Background The Tehuacán-Cuicatlán Valley is a region of outstanding biocultural diversity, harboring eight indigenous ethnic groups and a remarkable biodiversity in a territory 10,000 km2 extent. Ethnobotanical studies of the region are among the most complete in Mexico; contrarily, ethnozoological studies are still limited. But information on both flora and fauna use and management is relevant for understanding local cultural and ecological issues, and for planning integral strategies of biodiversity conservation. Our study focused on analyzing knowledge and use of animals and their relationship with faunistic management by the Cuicatec, an ancient human culture whose distribution is restricted to the region. We hypothesized that wild animals still have significant contributions to diet, medicine, and spiritual life of the Cuicatec people. In addition, we expected to find a gradient of interactions, from simple gathering and hunting to communitarian regulations of use, specialized management techniques and care, nurturing, and domestication of animals. Such gradient of management interactions would be influenced proportionally with cultural and economic values, viability maintenance, and scarcity of animals. Methods Our study was carried out in San Lorenzo Pápalo, Oaxaca. We conducted surveys and semi-structured and open interviews to people to document the Cuicatec nomenclature, classification, use, and management of fauna, as well as their perceptions about abundance, risks of disappearance, and availability of wild animals. We used images of animal species reported for the area as communication stimuli for confirming their local presence. Also, we recorded skins and skulls used as trophies and ornamental objects, pawprints, and excretes. Through free listing, we identified the most meaningful species of different animal groups. Whenever possible, we evaluated amounts of animals obtained from the wild, and for some species, we compared this information with data on their distribution and abundance evaluated through ecological sampling, to explore indicators on their sustainable use. Results The Cuicatec name all animals through the term i-ti and classify them in several groups of vertebrates, arthropods, and mollusks, some of them coinciding with the formal taxonomy and some others based on their social-cultural role. The most meaningful animals are 23 species of edible organisms, outstandingly the chicatana ants (Atta mexicana) and the cuetla Lepidoptera larvae (Arsenura armida), the lizard Sceloporus grammicus, and among the mammals some squirrels (Sciurus spp.), badgers (Nasua narica), and deer (Odocoileus virginianus). Some species were reported to be used for medicinal purposes, among them opossum (Didelphis spp.) and macaws (Ara militaris), used to ease childbirths, but this use almost disappeared. Local perception of availability of animal resources is associated to forest conservation. Regulations for protecting forests and the most used animal species were recorded; the rules are mainly associated to hunting and gathering seasons, respecting females of vertebrate species, and permits for gathering and hunting given by local authorities. Nurturing of animals was recorded in bird and mammal species, but in no case, their breeding was achieved. Conclusions Animals are important elements of the Cuicatec culture and subsistence, complementing their diet based on agricultural products. Animals used as medicine were still reported but substituted by modern medicine. There is a consensus about the need to conserve forests to ensure the maintenance of animals, which are valued as part of nature, the beauty of their territory, and culture. Communitarian regulations are the main ways for conserving fauna, but local techniques of animal management may help in designing conservation strategies.